1997
DOI: 10.1097/00007890-199702150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial to Evaluate Flush and Reperfusion Techniques in Liver Transplantation

Abstract: To determine the impact of different flush and reperfusion techniques on postreperfusion syndrome (PRS) and postoperative graft function, 100 transplants were randomly assigned into four groups as follows: group 1 (n=31), portal vein flush, no vena caval venting; group 2 (n=21), hepatic arterial flush, no vena caval venting; group 3 (n=29), portal vein flush with vena caval venting; and group 4 (n=19), hepatic artery flush with vena caval venting. Donor and recipient characteristics were similar. Extensive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…Times for ischemia, anastomosis and reperfusion are displayed in Table 1. During LTX 6,l (1-19) packed red cells, 10,7 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) fresh frozen plasma and 1,9 (1-6) packed platelets were used. A total of 3248,3 ml (1077-8500) were vacuumed off with the cellsaver device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Times for ischemia, anastomosis and reperfusion are displayed in Table 1. During LTX 6,l (1-19) packed red cells, 10,7 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) fresh frozen plasma and 1,9 (1-6) packed platelets were used. A total of 3248,3 ml (1077-8500) were vacuumed off with the cellsaver device.…”
Section: Resultsmentioning
confidence: 99%
“…Indications for liver transplantation were hepatitis B and/or C (1 3), alcoholic cirrhosis (12), hepatocellular carcinoma (8), primary biliary cirrhosis (2), cc-1-antitrypsin deficiency (2), autoimmune hepatitis (I) and Wilson's syndrome (1).…”
Section: Patientsmentioning
confidence: 99%
“…A randomized, prospective study [8] found that flush and reperfusion techniques do indeed have an impact on the incidence of PRS or on postoperative graft function.…”
Section: Discussionmentioning
confidence: 99%
“…Since Starzl described the first LTX [7], different kinds of reperfusion modalities have been tested [8][9][10] -we present a new approach. At our center, we perform LTX by the piggyback technique and without veno-venous bypass.…”
Section: Introductionmentioning
confidence: 99%
“…Results There were 85 patients in the pH ≤ 7.32 group and 385 patients in the pH > 7.32 group. The recovery of mean arterial pressure after hepatic artery reperfusion was [2][3][4]. Also, the administration of an alkalinizing agent through the IVC has been used to attempt to normalize the pH of the acidic preservation solution entering the systemic circulation before it reaches the sinus/AV nodes and coronary circulation [5].…”
Section: Introductionmentioning
confidence: 99%